Relationship between sports involvement and students' performance in Malaysian University / Norzaidi Mohd Daud, Akmal Syalwani Idris, Nazhatul Ashikin Abd Manaf and Fatin Adawiyah Mudzaffar - Idris, Akmal Syalwani; Abd Manaf, Nazhatul Ashikin; Mudzaffar, Fatin Adawiyah (Faculty of Business Management, 2013)
The purpose of this paper is to determine relationship between sports involvement and student's performance in Malaysian public university. Based on survey, this study suggested that the students who are involve actively in sports are also good in their study. It because, they have energetic body, an intelligent mind, and strong immune system. From having all of these, students tend to give full attention in class, being more dicipline, and be more creative in giving ideas. The results provide information about the pattern of how the students' performances can be increase by actively involve or participate in sports.